Compartment-specific dynamics of soil microbiota along a Pinus armandii plantation chronosequence in karst mountain ecosystems - He, Bin; Zhang, Ping; Bai, Xiaolong; Li, Wangjun; Zou, Shun (Frontiers in Microbiology, 2025)
Soil microbiomes play pivotal roles in mediating plant diversity maintenance by regulating multifunctional ecosystem services during plant development. However, how different stand age of plants influence soil microbial communities in various soil compartments remains poorly understood. Through Illumina-based 16S rRNA and ITS amplicon sequencing, we systematically investigated the successional trajectories of soil microbiome in Pinus armandii plantations spanning various developmental phases. Key findings revealed that stand age exerted a stronger influence on microbial restructuring than soil compartment, significantly altering community composition in both soil types. Alpha diversity (Shannon and Chao1 indices) exhibited a U-shaped trajectory with stand age, except for fungal Chao1 in bulk soil. While dominant bacterial and fungal phyla remained relatively stable, community composition displayed significant stage-dependent variations. Co-occurrence network analysis demonstrated lower fungal network complexity compared to bacterial networks, with rhizosphere soils harboring more intricate interactions compared to bulk soils. Community assembly mechanisms diverged: deterministic processes dominated bacterial assembly, whereas stochasticity governed fungal communities. Soil properties exerted significant influences on microbial composition and diversity: bacterial composition correlated strongly with pH and stoichiometric ratios (C/N, C/P, N/P), while fungal composition showed stronger associations with TN, TP, and AN. Our results demonstrate that P. armandii plantations maintain core phylum-level microbial populations while developing stage-specific diversity patterns. Crucially, bacteria and fungi exhibit divergent responses to stand development, highlighting their divergent ecological strategies in adapting to nutrient-limited karst ecosystems.